Analisis Daya Saing dan Faktor-faktor yang Mempengaruhi Ekspor Nenas Indonesia - Zainal, Sylvi Meidika; Tarumun, Suardi; Tety, Ermi (Journal of Agribusiness and Community Empowerment (JACE), 2021)
Pineapple is one of the leading commodities of the Indonesian horticultural sub-sector which has been known around the world and has the potential to be used as a mainstay export commodity in international trade. This research aims to analyze the competitiveness and factors that affect Indonesian pineapple exports in the international market. The analytical methods used are quantitative methods, namely estimation of competitiveness and factors that affect Indonesia's pineapple exports in several destination countries using Export Product Dynamic (EPD), multiple linear regression analysis, and classic assumption deviation tests. Indonesia's pineapple export destinations are Bahrain, Japan, Kuwait, Qatar, Singapore, and United Arab Emirates. Based on the estimated export product dynamic index (EPD) shows that the Indonesian pineapple export destination market position has strong competitiveness and occupies a Rising Star position so that it can continue to maintain its marketing, then occupy the position of Retreat then not potentially export due to the decrease in export share and declining export demand compared to competitive countries, namely Thailand and the Philippines. Then, based on the estimated multiple linear regression it is shown that Indonesian pineapple price to US dolar has a significant effect on Indonesian pineapple export volume, while Indonesian pineapple productivity and Indonesian pineapple export value have no significant effect on Indonesian pineapple export volume.